Optimization of C7/C8 splitter section of buali petrochemicals aromatic distillation unit with aspen plus software - Darabi, Mohsen; Mohammadiun, Hamid; Mohammadiun, Mohammad (International Journal of Scientific World, 2015)
In order to separating benzene and toluene (BT), in the aromatic distillation unit of BuAli petrochemical are used of a distillation column containing 55 trays. For condensing steam in the upper part of air cooler and down, a natural gas furnace,which the fuel is sharply 1 million cubic foot (MMscfd) is applied.It was equipped with two ultra-high energy consumption so that energy costs has been estimated 93384 in the year. in this study,According to the need of reduce energy consumption in consumer industries,especially oil, gas and petrochemical,we decided to investigate the energy recovery for aromatic distillation unit of BuAli petrochemical and with using of specialized software AspenPlus we provided a method for this purpose.In this regard,According to information taken from BuAli complex,several simulations were performed, and finally,the least investments expensive model with reducing energy consumption has been selected.The results of the selected model can be cited to remove completely power consumption of the air conditioner,45% reduction in fuel consumption in furnaces and heat exchangers,and ultimately58% reduction in the production of pollutant emissions that play important role in damaging the environment.